2010
DOI: 10.1002/pssb.200983818
|View full text |Cite
|
Sign up to set email alerts
|

Compact modeling of optically gated carbon nanotube field effect transistor

Abstract: BackgroundCarbon Nanotube Field Effect Transistors (CNTFETs) have high charge sensitivity at room temperature [1]. By using this sensitivity, some nonvolatile memory devices have been demonstrated with charge trapping in SiO 2 gate insulator [2,3]. Besides, a new design of synapse-like circuit requires a multi-level nonvolatile memory [4]. For this application, and according to its high charge sensitivity, Optically-Gated Carbon Nanotube Field Effect Transistor (OG-CNTFET) appears as a good candidate thanks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Macchione [23][24][25] reported a laser-writable and electrically erasable organic photoelectrochromic device based on methylene blue, which can change its color from blue to transparent on absorption of red He-Ne laser light and return to blue when induced by an external voltage. Liao [26] constructed a compact model of an optically gated carbon nanotube field effect transistor, which can perform reversible optical writing and electrical erasing operations. Furthermore, Hu [27] proposed a novel NIR light writing and electrical erasing device based on a SWNT-PDMS/Ni-PDMS composite bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…Macchione [23][24][25] reported a laser-writable and electrically erasable organic photoelectrochromic device based on methylene blue, which can change its color from blue to transparent on absorption of red He-Ne laser light and return to blue when induced by an external voltage. Liao [26] constructed a compact model of an optically gated carbon nanotube field effect transistor, which can perform reversible optical writing and electrical erasing operations. Furthermore, Hu [27] proposed a novel NIR light writing and electrical erasing device based on a SWNT-PDMS/Ni-PDMS composite bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…5À10 In particular, single-walled carbon nanotubes (SWNTs) have emerged as highly promising components of electronic and energy devices because of their high intrinsic charge-carrier mobility, high aspect ratio, and superior mechanical properties. 11À15 PSCs with SWNTs compose a promising heterostructure and were recently reported as a new platform for the next generation of optoelectronic devices, such as transistors, 16,17 photovoltaics, 18À20 photodetectors, 21 memories, 22 and sensors. 23 Several groups have demonstrated that thin film transistors (TFTs) and photovoltaics with a PSC/SWNT heterostructure as the channel material have improved the charge-carrier mobility and on-current.…”
mentioning
confidence: 99%
“…Printable polymer semiconductors (PSCs) have attracted considerable attention because of their potential applications in large-area, low-cost, flexible, and printed optoelectronics. However, the charge-carrier mobilities of PSC-based devices fabricated by inkjet printing are generally limited by hopping transport (lower conductivity) between polymer chains in disordered regions of such films. Therefore, the use of complementary heterostructures based on organic and inorganic semiconductors has been suggested as a potentially effective way to manipulate the optoelectronic properties of printed devices, as they may combine the desirable characteristics of both materials. In particular, single-walled carbon nanotubes (SWNTs) have emerged as highly promising components of electronic and energy devices because of their high intrinsic charge-carrier mobility, high aspect ratio, and superior mechanical properties. PSCs with SWNTs compose a promising heterostructure and were recently reported as a new platform for the next generation of optoelectronic devices, such as transistors, , photovoltaics, photodetectors, memories, and sensors …”
mentioning
confidence: 99%